Vectorizing unstructured mesh computations for many‐core architectures. (28th August 2015) - Reguly, I Z.; László, Endre; Mudalige, Gihan R.; Giles, Mike B.
Summary: Achieving optimal performance on the latest multi‐core and many‐core architectures increasingly depends on making efficient use of the hardware's vector units. This paper presents results on achieving high performance through vectorization on CPUs and the Xeon‐Phi on a key class of irregular applications: unstructured mesh computations. Using single instruction multiple thread (SIMT) and single instruction multiple data (SIMD) programming models, we show how unstructured mesh computations map to OpenCL or vector intrinsics through the use of code generation techniques in the OP2 Domain Specific Library and explore how irregular memory accesses and race conditions can be organized on different hardware. We benchmark Intel Xeon CPUs and the Xeon‐Phi, using a tsunami simulation and a representative CFD benchmark. Results are compared with previous work on CPUs and NVIDIA GPUs to provide a comparison of achievable performance on current many‐core systems. We show that auto‐vectorization and the OpenCL SIMT model do not map efficiently to CPU vector units because of vectorization issues and threading overheads. In contrast, using SIMD vector intrinsics imposes some restrictions and requires more involved programming techniques but results in efficient code and near‐optimal performance, two times faster than non‐vectorized code. We observe that the Xeon‐Phi does not provide good performance for these applications but is still comparable with a pair of mid‐range Xeon chips. Copyright © 2015 John Wiley & Sons, Ltd.